2005
DOI: 10.1007/s00122-005-2023-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a set of PCR-based anchor markers encompassing the tomato genome and evaluation of their usefulness for genetics and breeding experiments

Abstract: Tomato and potato expressed sequence tag (EST) sequences contained in the solanaceae genomics network (SGN) database were screened for simple sequence repeat (SSR) motifs. A total of 609 SSRs were identified and assayed on Solanum lycopersicum LA925 (formerly Lycopersicon esculentum) and S. pennellii LA716 (formerly L. pennellii). The SSRs that did not amplify, gave multiple band products, or did not exhibit a polymorphism that could be readily detected on standard agarose gels in either of these species were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(107 citation statements)
references
References 54 publications
7
95
2
3
Order By: Relevance
“…Several molecular marker viz. RFLP, RAPD, SSRs, ISSRs, AFLP and SNPsare presently available to assess the variability and diversity at molecular level, among which SSR markers are the most widely used (Frary et al, 2005). Earlier studies have reported the use of morphological and molecular markers viz.…”
Section: Issn: 2319-7706 Volume 7 Number 01 (2018)mentioning
confidence: 99%
“…Several molecular marker viz. RFLP, RAPD, SSRs, ISSRs, AFLP and SNPsare presently available to assess the variability and diversity at molecular level, among which SSR markers are the most widely used (Frary et al, 2005). Earlier studies have reported the use of morphological and molecular markers viz.…”
Section: Issn: 2319-7706 Volume 7 Number 01 (2018)mentioning
confidence: 99%
“…Subsequently, several types of DNA markers have been developed, e.g., random amplified polymorphic DNA (RAPD), simple sequence repeat (SSR) or microsatellite, amplified fragment length polymorphism (AFLP), cleaved amplified polymorphic sequence (CAPS), and single nucleotide polymorphism (SNP) markers. A total of 1,088 CAPS, 1,342 RFLP, 155 SSR, and 19 SNP markers have been mapped onto an interspecific genetic linkage map based on a cross between S. lycopersicum 'LA925' and S. pennellii 'LA716'; the Tomato-EXPEN 2000 map (Frary et al 2005;Fulton et al 2002;Shirasawa et al 2010a).…”
Section: Interspecific Mapsmentioning
confidence: 99%
“…Later, a whole genome sequencing strategy was also adopted, to cover the entire genome. In parallel with genome sequencing, the development of DNA markers and construction of highdensity genetic linkage maps were conducted to assist in the reconstruction of the whole genome structure by mapping (Frary et al 2005;Fulton et al 2002). The chloroplast and mitochondrial genomes were sequenced independently from the nuclear genome (Kahlau et al 2006).…”
mentioning
confidence: 99%
“…Most of these resources are also publicly available for the scientific community and are accessible via web (Table 2). Since the beginning of 1990s, the contribution of molecular markers and maps to tomato breeding and gene identification has been widely documented (Foolad, 2007;Frary et al, 2005;Gupta et al, 2009), and more than 15.000 different markers are collected in the SGN database, where markers can be searched by name, chromosome position and mapping population. Moreover, cytological and cytogenetic maps are also available, as well as a detailed physical map, which was the foundation for the tomato genome sequencing project (Mueller et al, 2005).…”
Section: Genetic and Genomic Resourcesmentioning
confidence: 99%